Subjectivity Analysis of Underground Incinerators: Focus on Academic and Industry Experts - Jae-hyuck Lee (MDPI AG, 2021)
Recently, incinerators have been shifted to underground complexes because of concerns regarding environmental pollution and declining land prices. In Korea, an underground waste incinerator has been built for the first time, with additional construction being expected in the near future. Therefore, a perception survey was conducted to acquire responses from South Korean experts regarding the impact of underground complex incinerators. The Q-methodology was used in the survey to examine various viewpoints. Academicians showed concerns regarding environmental effects of ground incinerators, and environmental and economic effects of underground complex incinerators; conversely, industrialists were concerned about civil complaints and administrative processing, indicating that the academicians were more concerned about scientific issues, whereas the industrialists were more concerned about democratic issues. Furthermore, both groups expressed concerns regarding land value and civil complaints of ground incinerators, safety issues and resultant social distrust of underground incinerators. The findings suggest that, to address the safety issues involving underground incinerator construction, governance by local experts is required for a holistic evaluation of environmental issues and economic feasibility of underground incinerators. To establish a link between science and democracy, measures for transparently sharing information are necessary.